A study of knowledge spillovers within Chinese mega-economic zones - Xiaobing Huang; Xinxin Meng; Meng Chen (Economics: The Open-Access, Open-Assessment Journal, 2022)
Using a prefectural level data, we shed the light on the knowledge spillovers within three mega-economic zones (MEZs) in China by adopting spatial econometric methods. We first examine the spillovers within all regions, and then the spillovers within the MEZs, and finally the spillovers from core cities. The results show that there are pronounced spillovers between cities in China, which is stronger between cities with high techno-proximity. Moreover, spillovers within the MEZs are found to be stronger but unequal. Spillovers between cities in the Pearl River Delta are the greatest among the MEZs, while the spillovers within Jing-jin-ji are the lowest. Eventually, Shenzhen outperforms Shanghai and Beijing in knowledge spillovers, whereas Beijing may even adversely affect the innovation of neighbors.
Keywords: 330; China; innovation; knowledge spillovers; mega-economic zones